Impact of the acuity circle model for liver allocation on multivisceral transplant candidates. Issue 2 (26th August 2021) - Ivanics, Tommy; Vianna, Rodrigo; Kubal, Chandrashekhar A.; Iyer, Kishore R.; Mazariegos, George V.; Matsumoto, Cal S.; Mangus, Richard; Beduschi, Thiago; Abouljoud, Marwan; Fridell, Jonathan A.; Nagai, Shunji
Abstract : Liver allocation was updated on February 4, 2020, replacing a Donor Service Area (DSA) with acuity circles (AC). The impact on waitlist outcomes for patients listed for combined liver‐intestine transplantation (multivisceral transplantation [MVT]) remains unknown. The Organ Procurement and Transplantation Network/United Network for Organ Sharing database was used to identify all candidates listed for both liver and intestine between January 1, 2018 and March 5, 2021. Two eras were defined: pre‐AC (2018–2020) and post‐AC (2020–2021). Outcomes included 90‐day waitlist mortality and transplant probability. A total of 127 adult and 104 pediatric MVT listings were identified. In adults, the 90‐day waitlist mortality was not statistically significantly different, but transplant probability was lower post‐AC. After risk‐adjustment, post‐AC was associated with a higher albeit not statistically significantly different mortality hazard (sub‐distribution hazard ratio[sHR]: 8.45, 95% CI: 0.96–74.05; p = .054), but a significantly lower transplant probability (sHR: 0.33, 95% CI: 0.15–0.75; p = .008). For pediatric patients, waitlist mortality and transplant probability were similar between eras. The proportion of patients who underwent transplant with exception points was lower post‐AC both in adult (44% to 9%; p = .04) and pediatric recipients (65% to 15%; p = .002). A lower transplant probability observed in adults listed for MVT may ultimately result in increased waitlist mortality. Efforts should be taken to ensure equitable organ allocation in this vulnerable patient population. Abstract : The recently implemented acuity circle‐based liver allocation in the United States is associated with a lower transplant probability for adults listed for multivisceral transplantation. Farmer comments on page 341 .